Integrated farming system models for arid and semiarid rainfed regions - Reddy, B Sahadeva; Rao, M M V Srinivasa; Padmalatha, Y (Indian Farming, 2021)
Strengthening of the traditional farming systems can be done with crop diversification, inclusion and improvement of livestock, horticulture crops, kitchen garden with primary and secondary processing, boundary plantations for improving the farm income of small holders in arid and semiarid regions. This also paves a way to meet the household balanced diet, improved recycling of nutrients and water besides increasing the on- farm employment for family. A productivity gain of 2 to 3 times and income gain of 3 to 5 times (enhancing the income of household to the level of at least ` 400-500/day) is possible with improved integrated farming systems in rainfed regions. Further, resource saving of 40-50% can also be ensured. Additional employment of 70-80% can be generated. Improved diversified systems also ensure household nutritional security. Most importantly, the improved integrated farming systems are better resilient than the single commodity-based production system, thus reduce climate risks in arid and semiarid regions.